An efficient synthesis of some new isolated and fused 2-oxo-2H-chromene derivatives as antimicrobial and antitumor agents - El-Shaaer, Hafez Mohamed (European Journal of Chemistry, 2013)
An efficient synthesis of the biologically active novel systems derived from the reaction of 4-methyl-2-oxo-2H-chromene-3-carbonitrile (1) with sodium hydroxide and/or DMF-DMA and cyclocondensation reactions of 4-[(E)-2-(dimethylamino)ethenyl]-2-oxo-2H-chromene-3-carbonitrile (5) with nitrogen nucleophilic reagents afforded the corresponding 4-iminochromeno[3,4-c]pyridine derivatives (6-14). The structures of the prepared compounds have been proved by elemental analysis, IR, 1H and 13C NMR and mass spectra. Significant antitumor activities in planta were observed for some of the prepared compounds.